Exploration of Social Model of Orchid Conservation for Strenghtening The Civic Values - Yayuk Hidayah; Latifa Nuraini; Lutfia Septiningrum (Actual Insight, 2026)
The social model of conservation has gained increasing relevance as an integrative framework for reinforcing cultural identity and civic values within local communities, particularly in the domains of environmental conservation and cultural preservation. This study examines the role of the social model of conservation in orchid conservation, emphasizing orchids not merely as biological resources but as cultural symbols that embody national awareness, collective responsibility, and civic care. Focusing on Batur Village, Yogyakarta, the research explores how community-based orchid conservation practices contribute to the strengthening of cultural values and citizenship at the local level. Employing a qualitative research design, this study adopts a case study approach supported by participatory observation, in-depth interviews with key stakeholders, and document analysis related to conservation initiatives and civic-cultural values. The findings reveal that the social conservation model implemented in Batur Village has effectively fostered community awareness of cultural heritage and civic responsibility through the symbolic and practical engagement with orchid conservation. Orchids function as a medium through which environmental stewardship, cultural continuity, and civic participation are cultivated and transmitted across community members. This study underscores the potential of socially grounded conservation models to bridge ecological sustainability with cultural and civic development. The findings offer important implications for policy formulation and conservation practices by highlighting the interconnections between nature conservation, cultural values, and citizenship education within Indonesia’s local context. Ultimately, this research contributes to broader discussions on sustainable development by demonstrating how conservation initiatives can simultaneously support environmental resilience and civic-cultural empowerment.